Sewage sludge treated with metal nanomaterials inhibits earthworm reproduction more strongly than sludge treated with metal metals in bulk/salt forms. Issue 1 (22nd December 2016) - Lahive, E.; Matzke, M.; Durenkamp, M.; Lawlor, A. J.; Thacker, S. A.; Pereira, M. G.; Spurgeon, D. J.; Unrine, J. M.; Svendsen, C.; Lofts, S.
Abstract : Sludge treated with ENMs caused greater effects on earthworm reproduction than sludge treated with metal salts. Abstract : Earthworms were exposed to soils amended with sewage sludges from a wastewater treatment plant (WWTP) treated with nanomaterials (ENMs) or metal/ionic salts. Sewage sludges were generated with either no metal added to the WWTP influent (control), ionic ZnO, AgNO3 and bulk (micron sized) TiO2 added (ionic metal-treated) or ZnO, Ag and TiO2 ENMs added (ENM-treated). A sandy-loam soil was amended with the treated sewage sludge and aged in outdoor lysimeters for six months. Earthworms were exposed to the aged mixtures and a dilution of the mixtures (using control soil–sludge mix). Separate earthworm exposures to as-synthesized ENM and ionic metals salts (Zn/Ag singly) were carried out in the same soil. Earthworm reproduction was depressed by 90% in the high-metal ENM treatment and by 22–27% in the ionic metal and low-metal ENM soil–sludge treatments. Based on total metal concentrations in the soil–sludges the as-synthesised metal salt and ENM exposures predicted Zn was driving observed toxicity in the soil–sludge more than Ag. Earthworms from the high-metal ENM treatment accumulated significantly more Ag than other treatments whereas total Zn concentrations in the earthworms were within the range for earthworm Zn regulation for all treatments. This study suggests that current Zn limits set to provide protection against ionic metal forms may not protect soil biota where metals are input to WWTP in the ENM form.